Semicondutores magnéticos diluídos do tipo (Zn, Co, Fe)O sintetizados por liofilização - Longen, Fabio Rogerio (2010)
The (Zn, Co, Fe)O system was synthesized for the first time by freeze-drying, starting from precursors such as zinc oxide, cobalt acetate and iron, varying the relative concentrations of the dopants (ie, cobalt and iron). The ceramic powders resulting from freeze-drying were heat treated in the free atmosphere, at different times and temperatures (250°C / 1h, 1000°C / 6 h and 1000°C / 12h), and in an atmosphere of H2 (350°C / 1h). The heat-treated samples were characterized by X-ray diffraction, Mössbauer spectroscopy (those containing iron) and alternating gradient magnetometry. The results showed significant differences for the specific limits of solubility for iron and cobalt in zincita that were invariably much higher for the latter. When the heat treatment was performed in free atmosphere, the (Zn, Co)O single-phase solid solutions, with up to 20%at.Co, and (Zn, Fe)O solid solutions, with up to 5%at.Fe, were obtained. On the other hand, samples synthesized in H2 atmosphere showed a higher solubility limit for cobalt (i.e, 25%at.Co) without, however, changing the solubility limit for iron earlier obtained in the free atmosphere. Magnetization measurements revealed ferromagnetic order at room temperature in samples with low dopant concentration. The saturation magnetization and the coercive field were higher in samples with iron, compared to those with the same cobalt content. This study discusses whether the origin of magnetism is in the (Zn, Co, Fe)O solid solutions or should be attributed to small secondary phase precipitates (e.g., spinels or cobalt oxides), not detectable by the X-ray diffraction and Mössbauer spectroscopy techniques.